1998
DOI: 10.1002/1529-0131(199809)41:9<1625::aid-art13>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum and clinical significance of autoantibodies against transfer RNA

Abstract: Novel autoantibodies against tRNAs or tRNA-associated proteins were identified in 28 sera. These autoantibodies appear to be distinct from anti-aminoacyl-tRNA synthetase antibodies and are associated with SLE and SS. The presence of anti-Ro/SSA and/or anti-La/SSB along with anti-tRNA antibodies is more strongly associated with recurrent erythema than is the presence of anti-Ro/SSA or anti-La/SSB alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Anti-EJ autoantibodies have been found to coexist with other autoantibodies, such as antinuclear antibodies (ANA) and Sjögren syndrome-associated autoantibodies anti-Ro/anti-La (SSA/SSB), or, in isolated cases, with autoantibodies directed against topoisomerase-1, Smith antigen or U1 ribonucleoprotein complex 8 9 19 20. The possibility of overlapping connective tissue disease-related ILD should be considered in patients with anti-EJ ARS syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-EJ autoantibodies have been found to coexist with other autoantibodies, such as antinuclear antibodies (ANA) and Sjögren syndrome-associated autoantibodies anti-Ro/anti-La (SSA/SSB), or, in isolated cases, with autoantibodies directed against topoisomerase-1, Smith antigen or U1 ribonucleoprotein complex 8 9 19 20. The possibility of overlapping connective tissue disease-related ILD should be considered in patients with anti-EJ ARS syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…by guest www.bloodjournal.org From aminoacyl-tRNA synthetase activity is also known to localize heavily to the microsomal subfraction in both human and mouse cells of hematopoietic origin. 32 In addition, there is extensive information in the literature implicating tRNA synthetases and their associated tRNAs as the autoreactive antigens in a vast array of autoimmune diseases, [33][34][35][36][37][38][39][40][41][42] suggesting preferential access of these molecules to MHC under conditions in which proteolytic damage might occur (ie, in the lysosomally derived compartments of DCs), thereby allowing the presentation of antigenic aminoacyl-tRNA synthetase peptides. Although it is beyond the scope of this manuscript to model the manner by which tRNA synthetases may participate in the comparison of class I and II antigenic peptide sequences, we implicated them mechanistically in this process by experiments using the glycyl-tRNA synthetase inhibitor ethanolamine.…”
Section: Discussionmentioning
confidence: 99%
“…Both tRNA-synthetases and tRNAs are the major autoantigens of a wide variety of autoimmune diseases including myositis, systemic lupus erythematosus, interstitial lung disease, and rheumatoid arthritis. [33][34][35][36][37][38][39][40][41][42] Moreover, our transcriptome analysis revealed that 8 tRNA-aminoacyl synthetases were differentially regulated among DCs doubly loaded with matched class I and II determinants (data not shown). Partly on the basis of these considerations, we generated the hypothesis that a recognisome might form between MHC class I and MHC class II in the postlysosomal microsome and further hypothesized that sequence comparisons within this recognisome could be mediated by extracytoplasmic tRNAs and/or their associated tRNA synthetases reported by Agris.…”
Section: Glycyl-trna Synthetase Inhibitor Ethanolamine Implicates Amimentioning
confidence: 99%
“…These antibodies are directed against synthetases, the cytoplasmic enzymes facilitating attachment of amino acids to their correspondent transfer RNAs (tRNAs). Clinical characteristics of the syndrome include myositis, Raynaud's phenomenon, fever, mechanic's hands and arthralgias [51][52][53].…”
Section: Antisynthetase Syndromementioning
confidence: 99%